Measurement of stiffness and damping coefficient of rubber tractor tires using dynamic cleat test based on point contact model - Yoo, Hogil; Oh, Jooseon; Chung, Woo-Jin; Han, Hyun-Woo; Kim, Ji-Tae; Park, Young-Jun; Park, Yoonna (International Journal of Agricultural and Biological Engineering, 2021)
The ride vibration of a tractor is affected mostly by the stiffness and damping coefficient of the seat suspension, cabin suspension, cabin rubber mounts, and rubber tires. However, in the case of rubber tractor tires, the stiffnesses and damping coefficients have not been researched adequately thus far, and it is not simple to measure these characteristics. In this study, a method for measuring and analyzing the stiffnesses and damping coefficients of rubber tractor tires, which were the input parameters for the tractor ride vibration simulation, was proposed. The cleat test, proposed in this study, did not require separate and complicated test equipment, unlike the conventional methods. The test was conducted simply by measuring acceleration under the driving conditions of the vehicle without detaching tires from the vehicle body or setting up additional test equipment. Based on the ground-vertical acceleration data obtained, the stiffness was calculated using the logarithmic decrement method, and the damping coefficient was calculated using least squares exponential curve fitting. The result of the cleat test indicated that the front tires had stiffnesses of 486.08-570.69 kN/m and damping coefficients of 4.02-4.52 kN·s/m; the rear tires had stiffnesses of 409.42-483.79 kN/m and damping coefficients of 2.21-2.67 kN·s/m. During the test, 40 mm height cleats were installed on the track and the speed of the tractor was set to 7 and 10 km/h, which were the most common speeds during the operation. This study is meaningful in that it has presented a new method that improves the practicality of results, reduces cost, and simplifies the test process for measuring the stiffnesses and damping coefficients of rubber tractor tires.Keywords: ride vibration, rubber tractor tire, stiffness, damping coefficient, cleat test, point contact modelDOI: 10.25165/j.ijabe.20211401.5799Citation: Yoo H, Oh J, Chung W-J, Han H-W, Kim J-T, Park Y-J, et al. Measurement of stiffness and damping coefficient of rubber tractor tires using dynamic cleat test based on point contact model. Int J Agric & Biol Eng, 2021; 14(1): 157–164.